2011
DOI: 10.3899/jrheum.100829
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Focal Erosions, Bone Mineral Density, and Parathyroid Hormone in Rheumatoid Arthritis

Abstract: Objective. To investigate the relationship among focal bone erosions and bone mineral density (BMD), 25(OH) vitamin D (25OHD), and parathyroid hormone (PTH) values in patients with rheumatoid arthritis (RA). Methods. The study included 1191 RA patients (1014 women, 177 men, mean age 58.9 +/- 11.1 yrs) participating in a multicenter, cross-sectional study. Results. Radiographic evidence of typical bony erosions on hands or forefeet was found in 64.1% of patients. In those with bone erosions as compared to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 31 publications
5
35
1
2
Order By: Relevance
“…Similar to this study, Rossini and his colleagues, 2011 [41] found vitamin D level to be very similar among the erosive and nonerosive RA. Low BMD level was only dependent on parathyroid hormone (PTH) values.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to this study, Rossini and his colleagues, 2011 [41] found vitamin D level to be very similar among the erosive and nonerosive RA. Low BMD level was only dependent on parathyroid hormone (PTH) values.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study has shown that ACPA can stimulate osteoclast differentiation, and that in ACPA-positive patients with RA there is more frequent evidence of bone loss and thinning of cortical thickness than in APCA-negative patients with RA (46)(47)(48). Recently, a significant correlation has been observed between RA related osteoporosis and risk of erosions (49,50). The incidence of new fragility fractures during GCs treatment in our cohort of patients was 12% in CTDs, 10% in PMR, and 23% in RA.…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…2 This result has been confirmed in a further paper, in which we observed that suppression of secondary hyperparathyroidism in autoimmune rheumatic patients was impaired with respect to patients affected by osteoarthritis after a cholecalciferol regimen used to correct hypovitaminosis D. 69 Similarly, in a multicentric study, RA patients with erosive evolution presented with higher PTH and lower BMD in comparison to patients with less aggressive arthritis, despite possessing similar vitamin D concentrations. 70 These observations raise the attention on the possible presence of a "relative hypovitaminosis D" in RA and in other inflammatory rheumatic diseases, which could explain the reduction in the physiological actions of this molecule; in these patients, indeed, the mechanisms that regulate PTH synthesis seem to be more refractory to vitamin D suppression.…”
Section: Vitamin D In Autoimmune Diseasesmentioning
confidence: 96%
“…We have demonstrated that only a high dose supplementation regimen (300,000 IU orally once) followed by a maintenance dose was superior, also if still suboptimal, in the correction of hypovitaminosis D and of secondary hyperparathyroidism in rheumatic patients. 70 …”
Section: Vitamin D In Autoimmune Diseasesmentioning
confidence: 97%